The value of the «nationality» in the concept of Slavophiles - E. V. Bobrovskih (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
Slavophile direction of the Russian sociopolitical thought that emerged in the nineteenth century attracts the interest of researchers even nowadays. It is connected not only with a meaningful component of the Slavophile concept, but with unusual methodological approaches in this direction. The original in this respect, according to the author, can be considered Slavophile approach to the study and interpretation of the concept of «nationality», which was widely discussed in the Russian socio-political thought of the XIX century.